Interleukin-1β, lipocalin 2 and nitric oxide synthase 2 are mechano-responsive mediators of mouse and human endothelial cell-osteoblast crosstalk - Vimal Veeriah; Angelo Zanniti; Riccardo Paone; Suvro Chatterjee; Nadia Rucci; Anna Teti; Mattia Capulli (2016)
Endothelial cells are spatially close to osteoblasts and regulate osteogenesis. Moreover, they are sensitive to mechanical stimuli, therefore we hypothesized that they are implicated in the regulation of bone metabolism during unloading. Conditioned media from endothelial cells (EC-CM) subjected to simulated microgravity (0.08g and 0.008g) increased osteoblast proliferation and decreased their differentiation compared to unit gravity (1g) EC-CM. Microgravity-EC-CM increased the expression of osteoblast Rankl and subsequent osteoclastogenesis, and induced the osteoblast de-differentiating factor, Lipocalin 2 (Lcn2), whose downregulation recovered osteoblast activity, decreased Rankl expression and reduced osteoclastogenesis. Microgravity-EC-CM enhanced osteoblast NO-Synthase2 (NOS2) and CycloOXygenase2 (COX2) expression. Inhibition of NOS2 or NO signaling reduced osteoblast proliferation and rescued their differentiation. Nuclear translocation of the Lcn2/NOS2 transcription factor, NF-κB, occurred in microgravity-EC-CM-treated osteoblasts and in microgravity-treated endothelial cells, alongside high expression of the NF-κB activator, IL-1β. IL-1β depletion and NF-κB inhibition reduced osteoblast proliferation and rescued differentiation. Lcn2 and NOS2 were incremented in ex vivo calvarias cultured in microgravity-EC-CM, and in vivo tibias and calvarias injected with microgravity-EC-CM. Furthermore, tibias of botulin A toxin-treated and tail-suspended mice, which featured unloading and decreased bone mass, showed higher expression of IL-1β, Lcn2 and Nos2, suggesting their pathophysiologic involvement in endothelial cell-osteoblast crosstalk.